महाकवि गोविन्द पै - Sunitha Bai, L. (Konkani Language and Cultural Foundation, Mangaluru, 2008)
This book is a biography of Mahakavi Govinda Pai
Mahakavi Govinda Pai
Keywords: Konkani; महाकवि गोविन्द पै; Mahakavi Govinda Pai; Biography; Konkani; Konkani